PEMBERDAYAAN PEREMPUAN PURWAKARTA: MERETAS JALAN KEMANDIRIAN DAN KESETARAAN MELALUI SEKOPER CINTA DI DESA CIPANCUR KECAMATAN CIBATU KABUPATEN PURWAKARTA - Jumiati, Eti (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
The purpose of the implementation of this community service is to empower women in Cipancur Village, Cibatu District, Purwakarta Regency to be able to hack the path of independence and equality through the Sekoper Cinta Program. The number of training participants was 100 people, in accordance with the target, namely women who still have shortcomings in self-competence in terms of knowledge, skills and attitudes. The number of training hours was 21 materials X 2.5 hours = 52.5 training hours of both theory and practice. The results of the training: there was a significant change in competence (knowledge, skills and attitudes), the evaluation was carried out by comparing the pretest and posttest both in writing and in practice and judging from the attendance of participants which reached 95%, meaning that women in Cipancur village have the enthusiasm to change.